Levels of T4 and TSH in mother’s blood and in cord blood at the time of delivery - Agrawal, K; Paudel, BH; Singh, PN; Majhi, S; Pokhrel, H; Upadhayay, N (Health Renaissance, 2013)
Background: In conditions of maternal iodine deficiency, the frequency distribution of neonatal thyroid stimulating hormone (TSH) is shifted towards elevated values. Elevated serum TSH in the neonates indicates insufficient supply of thyroid hormones to the neonates, a major complication of iodine deficiency. Objectives: To determine the cord blood serum T4 and TSH levels and interrelationships with maternal thyroid hormones. Method: cord blood serum T4 and TSH levels of 45 consecutive newborns born at BPKIHS, Dharan, Nepal and maternal T4 and TSH levels were analyzed using ELISA based kits. Results: The mean age of mothers was 23.73± 3.86 years and average weight of the neonates was 3.038±0.45 Kg. The median levels of maternal and neonatal T4 were 1.09 ng/dl and 1.26 ng/ dl respectively. The corresponding median TSH levels were 3.71 mIU/L and 11.9 mIU/L. The maternal and neonatal levels of T4 were positively correlated. In 36 mothers who had TSH level within euthyroid range (0.3-6.2 mIU/L, Thyroid lab of BPKIHS), 22 neonates (61.11%) had TSH levels above 10 mIU/L. Among 9 mothers having TSH levels above 6.2 mIU/L, 7 (77.77%) neonates had TSH levels above 10 mIU/L. Conclusion: Overall 29 (64.44%) neonates had TSH level above 10 mIU/L which indicates mild degree of iodine deficiency. Iodine supplementation is required before pregnancy in majority of women of reproductive age. Health Renaissance, January-April 2013; Vol. 11 No.1; 6-10 DOI: http://dx.doi.org/10.3126/hren.v11i1.7593